2013
DOI: 10.1111/dmcn.12345
|View full text |Cite
|
Sign up to set email alerts
|

Changes in saccadic eye movement and memory function after mild closed head injury in children

Abstract: ABBREVIATIONS BRIEFBehavior Rating Inventory of Executive Function ImPACT Immediate post-concussion assessment and cognitive testing mCHI Mild closed head injury mTBI Mild traumatic brain injury Peabody Picture Vocabulary Test, 4th edition AIM The aim of this study was to determine whether volitional saccadic impairments are present in children with mild closed head injury (mCHI) and whether these deficits are predictive of ongoing cognitive impairment.METHOD We analysed a sample of 26 children with mCHI (20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Historically, decreased memory function in TBI populations has been reported to reflect deficits in monitoring and control processes that result from damage sustained to PFC regions (Di Stefano et al, 2000). Considering that maturation of PFC continues into early adulthood and that PFC development mediates age-related increase in memory-related monitoring and control processes (Ofen, 2012;Ofen, Chai, Schuil, Whitfield-Gabrieli, & Gabrieli, 2012), TBI-related insult to PFC during childhood likely results in long-term deficits in memory functioning (Phillipou, Douglas, Krieser, Ayton, & Abel, 2013). However, in addition to deficits related to damage to PFC, there is growing evidence that the hippocampal formation is also adversely affected by TBI (Ariza et al, 2006;Tasker et al, 2005;Wilde et al, 2007).…”
Section: Memory After Tbi: Relation To Hippocampal Volumementioning
confidence: 99%
“…Historically, decreased memory function in TBI populations has been reported to reflect deficits in monitoring and control processes that result from damage sustained to PFC regions (Di Stefano et al, 2000). Considering that maturation of PFC continues into early adulthood and that PFC development mediates age-related increase in memory-related monitoring and control processes (Ofen, 2012;Ofen, Chai, Schuil, Whitfield-Gabrieli, & Gabrieli, 2012), TBI-related insult to PFC during childhood likely results in long-term deficits in memory functioning (Phillipou, Douglas, Krieser, Ayton, & Abel, 2013). However, in addition to deficits related to damage to PFC, there is growing evidence that the hippocampal formation is also adversely affected by TBI (Ariza et al, 2006;Tasker et al, 2005;Wilde et al, 2007).…”
Section: Memory After Tbi: Relation To Hippocampal Volumementioning
confidence: 99%
“…Impairment of convergence can occur but commonly resolves spontaneously (Poggi et al 2000 ;Barlow et al 2005 ;Kedar et al 2006 ). Changes in volitional saccadic eye movements may be present after mild closed head injury in children, which may persistently impair visual processing (Phillipou et al 2014 ). The spectrum of severity ranges from total loss of vision, to any degree of impairment of visual acuity and visual fi eld loss, through to visual perceptual dysfunction, notably in our experience, the typical pattern of 'dorsal stream dysfunction' due to bilateral posterior parietal dysfunction, culminating in impaired visual search, which may be associated with impaired visual guidance of movement.…”
Section: Other Aetiologiesmentioning
confidence: 99%
“…Antisaccade latency returns to normal after 1 week post-mTBI ( 19 , 20 ), but accuracy differences have been documented up to few months postinjury ( 20 ). Some studies have shown that antisaccade accuracy appears to be impaired in the acute stages, with patients making more errors than controls ( 19 21 ); others indicate better performance ( 22 ). Only one study was found to relate acute antisaccade performance to neuroimaging, and the focus was mainly on functional performance ( 21 ).…”
Section: Introductionmentioning
confidence: 99%